PEMANFAATAN RAJANGAN KAYU SENGON DAN PLASTIK SEBAGAI BAHAN BAKU PEMBUATAN PAPAN PARTIKEL - , Danang Puji Nugraha, S.Pd ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Natural resources had multifarious in Indonesia manner, especially forest wood, the happening of fast growth affect at wood waste equal to 65% and plastic 11%. With solid waste technology of plastic and wood can be made by wood slices and plastic to be exploited to to become particle board. Raw material in this research is wood slices of sengon plastic and with glue of formaldehyde urea, to yield good particle board. This research aim to exploit wood slices of sengon, plastic with glue of formaldehyde urea become particle board. This Research method is done/conducted by preparation of materials, mix use comparison of mixture that is 59% wood slices of sengon : 39% plastic rajangan : 2% Urea Formaldehyde, making of mate 30 x cm 30 x cm 1 cm, pengepresan of heat with warm-up temperature 170 Âº C. Materials in deliberating each is later